Implementasi Pembelajaran Moral Anak Usia Dini di TK Al Mardhiyyah Samarinda - Andi Aslindah; Yuni Ika Pratiwi (LP. Ma'arif Janggan Magetan, 2024)
This research is motivated by the importance of applying moral learning to children from an early age because it is hoped that the characters they acquire will become habits that stick with them when they grow up. However, learning methods at PAUD have striking differences compared to other school levels. The implementation of learning in PAUD must be adapted to the stage of development and learning principles that adapt to the characteristics and needs of children. The aim of this research is to determine the implementation of moral learning in early childhood at Al-Mardhiyyah Kindergarten Samarinda. The approach used is descriptive qualitative with data collection tools, namely observation, documentation and interviews with the subjects, namely 2 class teachers and the school principal. In implementing moral learning in early childhood at Al-Mardhiyyah Kindergarten Samarinda, careful, mature and systematic planning has been carried out for the success of moral learning among its students. Likewise, the implementation of moral learning activities has been carried out with a consistent and integrated approach in children's daily activities. In this research, it was found that the moral values ​​of honesty, responsibility, politeness, respect, caring and patience have been implemented and integrated in the learning process, in accordance with the learning methods at Al-Mardhiyyah Kindergarten, namely through example, habituation and repetition. which is repetitive. Al-Mardhiyyah Kindergarten also continues to carry out evaluations to ensure that the learning programs implemented are effective in shaping children's moral behavior.